Bioethics and Climate Change: A Response to Macpherson and Valles. (10th May 2016) - Resnik, David B.
Abstract: Two articles published in Bioethics recently have explored the ways that bioethics can contribute to the climate change debate. Cheryl Cox Macpherson argues that bioethicists can play an important role in the climate change debate by helping the public to better understand the values at stake and the trade‐offs that must be made in individual and social choices, and Sean Valles claims that bioethicists can contribute to the debate by framing the issues in terms of the public health impacts of climate change. While Macpherson and Valles make valid points concerning a potential role for bioethics in the climate change debate, it is important to recognize that much more than ethical analysis and reflection will be needed to significantly impact public attitudes and government policies.